Marshall parameters for quality control of hot mix asphalt after pavement construction - Bojorque Iñeguez , Jaime; Flores, Cristian; V´ásquez, Mario (Revista de la Construcción. Journal of Construction, 2019)
Highways have been and are built using Hot Mix Asphalt (HMA) as surface layer. The most common HMA design procedure is the Marshall Method, a method also used for quality control (QC) at the time of road construction. Due to several factors, sometimes it is not possible to sample the surface layer when constructed. When this occurs, QC is performed after construction by analyzing cores. Current regulations, however, fail having clear procedures regarding the collection and analysis of pavement cores after the complete placement of the asphalt mixture. For this reason, this study proposes a comparative analysis of Marshall parameters, mixture densities, and aggregates gradation obtained from specimens obtained during construction, versus cores samples extracted 30 and 60 days later. The research revealed that all the parameters measured on core samples, except flow, could be used to approve asphalt paving works after its construction.